Mechanisms Underlying the Antidiabetic Activities of Polyphenolic Compounds: A Review - Nie, Tina; Cooper, Garth J. S. (Frontiers in Pharmacology, 2021)
Polyphenolic compounds are thought to show considerable promise for the treatment of various metabolic disorders, including type 2 diabetes mellitus (T2DM). This review addresses evidence from in vitro, in vivo, and clinical studies for the antidiabetic effects of certain polyphenolic compounds. We focus on the role of cytotoxic human amylin (hA) aggregates in the pathogenesis of T2DM, and how polyphenols can ameliorate this process by suppressing or modifying their formation. Small, soluble amylin oligomers elicit cytotoxicity in pancreatic islet β-cells and may thus cause β-cell disruption in T2DM. Amylin oligomers may also contribute to oxidative stress and inflammation that lead to the triggering of β-cell apoptosis. Polyphenols may exert antidiabetic effects via their ability to inhibit hA aggregation, and to modulate oxidative stress, inflammation, and other pathways that are β-cell-protective or insulin-sensitizing. There is evidence that their ability to inhibit and destabilize self-assembly by hA requires aromatic molecular structures that bind to misfolding monomers/oligomers, coupled with adjacent hydroxyl groups present on single phenyl rings. Thus, these multifunctional compounds have the potential to be effective against the pleiotropic mechanisms of T2DM. However, substantial further research will be required before it can be determined whether a polyphenol-based molecular entity can be used as a therapeutic for type 2 diabetes.